Nakşbendî meşâyihinden Hacı Feyzullah Efendi ve tasavvufî görüşleri - Kaymakçı, Fatma (My University, 2019)
Nakşbendî meşâyihinden Hacı Feyzullah Efendi’nin (v. 1876) hayâtını ve tasavvufî görüşlerini konu alan bu çalışma üç bölümden oluşmaktadır. Çalışmamızın “Şeyh Feyzullah Efendi” başlığını taşıyan birinci bölümünde Feyzullah Efendi’nin biyografisi oluşturulmaya çalışılmış, tasavvuf târihindeki yeri ve karıştığı iddia edilen Kuleli Vakʽası’ndaki konumu ele alınmıştır. Yeni bilgiler ışığında Feyzullah Efendi Tekkesi’nin târihî süreci üzerinde durulmuştur. “Şeyh Feyzullah Efendi’nin Tasavvufî Şahsiyeti ve Görüşleri” başlıklı ikinci bölümde Feyzullah Efendi’nin mürşidleri ve halîfeleri hakkında aktarılmış, günümüze ulaşan tek eseri İlm-i Hâl-i Hakîkat’ten hareketle tasavvufî görüşleri ortaya konulmuştur. “İbnülemin Bey’in Hacı Feyzullah Efendi Hakkındaki Yazma Mecmûası” başlıklı üçüncü bölümde ise Feyzullah Efendi’nin hayâtına dâir en kapsamlı bilgileri ve İlm-i Hâl-i Hakîkat’i ihtivâ etmesi dolayısıyle İstanbul Üniversitesi Nâdir Eserler Kütüphânesi İbnülemin Koleksiyonu’nda yer alan 2760 numarada kayıtlı yazma mecmûanın çevrimyazısına yer verilmiştir.

This work, which covers the life and Sufi views of Haji Feyzullah Efendi (d. 1876) from Naqshbandi sheikhes, consists of three parts. In the first part of our study titled “Sheikh Feyzullah Efendi”, that was a biography of Feyzullah Efendi was tried to be created and his place in the history of sufism and his position in the Kuleli case, which is alleged to have been involved, was discussed. In addition, the historical process of a dervish lodge which named Feyzullah Efendi Tekke was emphasized in the light of new information. In the second chapter titled “The Sufi personality and opinions of Sheikh Feyzullah Efendi”, general information about the murshids and caliphs of Feyzullah Efendi was conveyed and the sufi views were put forward based on his only works to date named Ilm-i Hâl-i Hakîkat .The third chapter, which is titled “Ibnülemin Bey’s Journal of writing about Haji Feyzullah Efendi”, contains the most comprehensive information about the life of Feyzullah Efendi and Ilm-i Hâl-i Hakîkat, so the translation of the manuscript recorded in the Istanbul University Rare Works Library Ibnülemin collection with number 2760.
Keywords: Feyzullah Efendi; Ilm-i Hal-i Hakikat; Islam; İlm-i Hâl-i Hakîkat; İslam; Kuleli case; Kuleli Vakʽası Feyzullah Efendi; Nakşbendiyye; Naqsbandiyya; Sufism; Tasavvuf